Female Farmworkers Participation in the Cultivation of Madurese Local Maize at Pakaan Laok Village - Vaundrawati Dheananda Salsadyra; Taufik R D A Nugroho; Teti Sugiarti (Universitas Muhammadiyah Malang, 2022)
The role of women in the agricultural sector in developing countries is essential. Female farmworkers have dominated the workforce in corn cultivation; nevertheless, it is challenging to apply dissemination materials on corn planting as these workers still use their agricultural insight from generation to generation. This study aimed to determine: 1) the characteristics of female farmworkers who participate in local corn cultivation, 2) the level of women's participation in local corn cultivation activities, and 3) the factors that influence women's participation in local corn cultivation.The research lsite is in Pakaan Laok Village, which was determined by purposive technique. Sample-taking was by simple random sampling. Methods of data analysis used descriptive analysis and multiple linear regression. The results showed that most female farmworkers' age ranges between 40-54 years, did not attend school, and the income ranges between Rp. 0-667,000 per planting season, land ownership status is individual ownership, and their economic motivation is to help their husbands. The variables of education, farm income, and economic motivation partially affect women's participation. In contrast, age and land ownership do not partially affect the participation rate of female farmworkers. The level of participation of women farmers at the planning stage is in a low category, and at the implementation, the stage is in a very high category